REVIEW OF THE APPLICATION OF ANAMBRA STATE PUBLIC PROCUREMENT LAW IN BUDGET IMPLEMENTATION BY THE MINISTRY OF WORKS - EZENWEGBU Nchedochukwu Chinwendu,; ANAZODO Rosemary, (International Journal of Psychosocial Rehabilitation, 2020)
This study is on review of Due process application in budget implementation of Anambra state ministry of works, Awka. The study was motivated by the pronounced spare of infrastructural decay in the state and the disbursement of the state’s capital budget. As indicated, the examination is done from the platform of the activities of Ministry of works, Awka. The research methods used in this study is “survey” because the phenomenon under research investigation was of the present and this method ultimately deals with the situation under investigation. The population of the study is seven hundred and seventy-one (771) which comprises of the professionals, management staff and senior staff of the Anambra Ministry of Works, Awka and registered contractors involve in execution of capital budgets under the Ministry. Sample size of three hundred and seventeen (317) was determined using Taro Yammen of 1964. Tools of data collection used were structured closed ended questionnaires. Quantitative data collected was analyzed by the use of descriptive statistics using the Statistical Package for Social Sciences (SPSS) and presented through percentages, means and frequencies. Relevant literature on public procurement Act, Public procurement Law and Budget were also reviewed. In the course of testing the three hypotheses, we applied chi-square. The Chi-square was used to test if Government of Anambra state has effectively implemented the laws on procurement which it enacted; if Due process mechanism has a significant impact on budget implementation in Anambra state ministry of works, Awka; If there is high level of. awareness of the public procurement Law in Anambra ministry of works, Awka. The study revealed that delay in the certification of public procurement and release of contract documents hampers effective implementation of the procurement Law. The study also revealed that delay in the payment after contract completion was a major challenge. Against the revealed backdrop, the study recommends the critical need for the Ministry and or Due Process Unit to shorten bureaucracies in the approval process. The study further recommends for prompt payment of completed contracts to guard against unnecessary liabilities.